Bacterial coaggregation’s role in water disinfection resistance - Afonso, Ana C.; Gomes, Inês B.; J. Saavedra, Maria; Simões, Lúcia C.; Simões, Manuel (Scientific Letters, 2024)
Background: In the realm of water treatment and public health, the interplay between microorganisms and disinfection processes represents a constant and dynamic challenge [1]. As society strives to ensure the availability of safe and clean water, understanding the factors contributing to bacterial resistance to water disinfection emerges as a critical area of research [1]. Among these factors, the phenomenon of bacterial coaggregation has gained increasing attention for its pivotal role in shaping microbial communities and influencing the effectiveness of disinfection strategies [2]. Objective: This work aims to elucidate the intricate relationship between bacterial coaggregation and resistance to water disinfection. Methods: Biofilms of the emerging drinking water (DW) pathogen Stenotrophomonas maltophilia [3,4] were formed on polyvinyl chloride (PVC) coupons for 7 days and studied for their resistance to sodium hypochlorite disinfection when co-cultured with two strains from the DW context: one exhibiting coaggregation behavior (Delftia acidovorans 005P) and another without coaggregation tendencies (D. acidovorans 009P). Results: It was observed that high doses of free chlorine (> 10x MBC) were not able to completely kill biofilm bacteria within 30 minutes of disinfection. However, biofilms that combined S. maltophilia with D. acidovorans 005P (coaggregating strain) showed greater resistance to disinfection. In addition, the biofilms that contained the coaggregating strain were also those that presented a greater content of extracellular polymeric substances (EPS), namely proteins and polysaccharides, and a greater thickness. Conclusions: It is known that coaggregation is mediated by protein-saccharide interactions and that in this case, they may be contributing to the biofilm’s tolerance to disinfection [1,5]. Thus, understanding the role of bacterial coaggregation in disinfection resistance is pivotal for developing innovative strategies that can effectively combat the persistence of pathogenic microorganisms and safeguard public health in an increasingly complex and interconnected world.